2017
DOI: 10.1007/s10439-016-1787-z
|View full text |Cite|
|
Sign up to set email alerts
|

Deformability of Human Mesenchymal Stem Cells Is Dependent on Vimentin Intermediate Filaments

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
(76 reference statements)
2
23
0
Order By: Relevance
“…Some studies have demonstrated that the changes of cytoskeleton and adhesion ability influenced the invasive potential and motility of cancer cells . Our results suggested that AmotP130 expression status was related with the arrangements of the cytoskeleton.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Some studies have demonstrated that the changes of cytoskeleton and adhesion ability influenced the invasive potential and motility of cancer cells . Our results suggested that AmotP130 expression status was related with the arrangements of the cytoskeleton.…”
Section: Resultssupporting
confidence: 55%
“…Some studies have demonstrated that the changes of cytoskeleton and adhesion ability influenced the invasive potential and motility of cancer cells. 26,27 Our results suggested that AmotP130 expression status was related with the arrangements of the cytoskeleton. Therefore, we measured the invasion ability and motility of of the cell at 30 minutes, while the MM231OE cells showed no obvious protrusions until 1.5 hours ( Figure 3E).…”
Section: Amotp130 Affected Cell Motor Ability and Invasion Ability mentioning
confidence: 63%
“…It is generally considered that vimentin forms passive scaffolding, which mechanically transmits the pulling forces generated by actomyosin but also protects the cells from fast and large mechanically induced deformation . However, actin microfilaments and microtubules can compensate for its action when it is deficient . Vimentin also plays a role in actin‐driven nucleus positioning during migration .…”
Section: Nuclear Structures and Nuclear Cytoskeletal Interactionsmentioning
confidence: 99%
“…Vimentin is a widely expressed and highly conserved 57-kD protein that constitutes type III intermediate filaments and is constitutively expressed in mesenchymal cells, being important in their development, integrity, and maintenance [93], and modifications in these intermediate filaments can lead to morphological and functional changes [94,95]. Vimentin is o en identified on the surface and intracellular filament of MSCs and different tissues, namely the OM [96] and on olfactory receptor neurons which continue to express this marker unlike other postmitotic neurons that cease vimentin expression as nerve development progresses [97].…”
Section: Immunohistochemical Analysismentioning
confidence: 99%